Physico-Chemical Water Quality Assessment of Sajwai Pond, Barwani District, Madhya Pradesh, India - Mandloi, Anjali; Gupta, Anuja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Water is one of the most vital elements for life on Earth, playing a critical role in maintaining ecological balance, supporting biodiversity, and sustaining human activities. Freshwater ecosystems can be broadly classified into lentic systems, which include still waters such as lakes, ponds, and reservoirs, and lotic systems, represented by flowing waters like rivers and streams. This study investigates the seasonal variations in the water quality of Sajwai Pond, a freshwater body located in Barwani district, Madhya Pradesh, India. By analyzing key parameters such as temperature, pH, turbidity, total dissolved solids (TDS), chloride, total hardness, alkalinity, magnesium, calcium, nitrate, biochemical oxygen demand (BOD), dissolved oxygen (DO), and free carbon dioxide across winter, monsoon, and summer seasons, the research offers insights into the pond’s ecological health and usability. The findings reveal significant seasonal trends: increased turbidity and nutrient concentrations during the monsoon due to surface runoff, higher ion concentrations in summer driven by evaporation, and stable conditions during winter. Despite these fluctuations, all parameters remained within acceptable limits for irrigation, domestic use, and the survival of aquatic life. This highlights the resilience and functionality of Sajwai Pond. However, the study emphasizes the importance of proactive measures, such as regular water quality monitoring and conservation initiatives, to manage challenges like nutrient loading and sedimentation. These efforts will help maintain the ecological balance of small but vital freshwater ecosystems like Sajwai Pond.